Assessing University Students’ Knowledge and Perceptions of Sexually Transmitted Infections: Sources of Information, Risk Awareness, and Educational Implications - Makhaye, Nontando; Thembane, Nokukhanya; Jaya, Ziningi (Student’s Journal of Health Research Africa, 2025)
Introduction There are over 376 million new cases of sexually transmitted infections (STIs) annually, with chlamydia, gonorrhoea, syphilis, trichomoniasis, and human papillomavirus being the most common. Investigating STIs among university students is vital due to high-risk behaviour, characteristic of university students, which increases the risk of transmission along with their long-term health risk. This study aimed to examine the knowledge and perceptions about STIs and their prevalence among students at Mangosuthu University of Technology. Method A total of 284 students participated in this study. Data collection was conducted using electronic and paper-based surveys depending on participant preference. The survey comprised of questions focused on demographics and practices, evaluating on STI knowledge, and students’ perceived risk of infection with STIs. STI prevalence statistics were obtained from the university clinic. Results The majority of participants perceived their STI knowledge as either "Good" (44.37%) or "Excellent" (25%), with a small proportion rating their knowledge as "Scarce" (19.72%). Sources of information included the internet (35.56%), teachers (28.17%), and healthcare professionals (22.18%). In terms of risk awareness, most students perceived themselves at "Moderate" (42.9%) or "A lot" (37%) risk of contracting an STI. Notably, no statistically significant differences in STI knowledge were found across gender or age groups. More female students were treated for STIs than their male counterparts. Conclusion The findings emphasize the need for more targeted educational approaches, particularly gender-sensitive interventions, and underscore the importance of combining multiple educational sources, including formal curricula, peer education, and digital platforms, to improve STI knowledge and risk awareness. Recommendations Future studies should explore the intersection between self-perceived knowledge, actual awareness, and testing behaviours to better understand how STI education can be optimized for diverse student populations.